Marguerite de Roberval et l’imaginaire colonial de l’affrontement entre les femmes et les bêtes sauvages - Zoé Marty (Les Cahiers de l'École du Louvre)
The story of Marguerite de Roberval, as it was told in the 16th century, includes a bear-hunting episode that differs from the traditions in which women and wild beasts are placed in opposition. In spite of this particular anomaly, this female figure was part of the imaginative universe of the pioneers when it was imported into the Atlantic context of the 19th century. The imperatives of survival and domination that characterised these territories were favourable to the exaltation of female figures whose violence was rendered apparent in their confrontation with wild animals and the manufacture of their bodies. This was the case of Martha Maxwell, a hunter and taxidermist for whom the rifle was a creative tool. This article attempts to analyse the significance of Roberval in relation to the practices of certain women during the second half of the 19th century in the territories of the Atlantic.